2012
DOI: 10.1002/dvdy.23799
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activities of Rho and Rac GTPases underlie the transition from neural crest delamination to migration

Abstract: In the context of crest delamination and migration, activities of Rho and Rac are differential, sequential, and antagonistic. Furthermore, transient inhibition of Rac1 that delays the onset of crest dispersion raises the possibility that the fate of trunk neural progenitors might be restricted prior to migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 62 publications
1
37
1
1
Order By: Relevance
“…Numerous studies have shown that neural crest derivatives are formed in a ventral-to-dorsal sequence (Baker et al, 1997; Krispin et al, 2010; Lumsden et al, 1991; McKinney et al, 2013; Nitzan et al, 2013; Osumi-Yamashita et al, 1994; Shoval and Kalcheim, 2012). It is interesting to note that, in the study by Lumsden et al (Lumsden et al, 1991), although no attempt was made to label distinct regions of the neural fold, the authors found that, when the neural fold in the midbrain was labeled at early stages, only labeling of the ectomesenchyme was observed in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that neural crest derivatives are formed in a ventral-to-dorsal sequence (Baker et al, 1997; Krispin et al, 2010; Lumsden et al, 1991; McKinney et al, 2013; Nitzan et al, 2013; Osumi-Yamashita et al, 1994; Shoval and Kalcheim, 2012). It is interesting to note that, in the study by Lumsden et al (Lumsden et al, 1991), although no attempt was made to label distinct regions of the neural fold, the authors found that, when the neural fold in the midbrain was labeled at early stages, only labeling of the ectomesenchyme was observed in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental heterogeneity exists within neural crest-derived populations, at least when they first emerge from the neural epithelium in vitro (Henion and Weston, 1997) and in vivo (Krispin et al, 2010; McKinney et al, 2013; Nitzan et al, 2013; Shoval and Kalcheim, 2012). Moreover, a population of mesenchyme cells precociously emerges from lateral cranial neural fold epithelium and enters the branchial arches before other cells emerge from the neural tube (Hill and Watson, 1958; Nichols, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…These signals are capable of activating numerous intracellular pathways; however, convergent regulation of common downstream components, such as Rho and Rac, serves as a key integration point (Berndt, Clay, Langenberg, & Halloran, 2008; Clay & Halloran, 2014; Liu & Jessell, 1998; Shoval & Kalcheim, 2012; Theveneau & Mayor, 2012). Newly developed high-resolution imaging techniques and genetic tools will continue to provide unique insight into how entire populations of cells are guided into distinct migratory routes and destinations during embryogenesis (Clay & Halloran, 2010).…”
Section: Molecular Regulators Of Neural Crest Migrationmentioning
confidence: 99%
“…In addition, RhoV and RhoU, which do not signal through ROCK, are expressed in Xenopus and chick NCCs, and have functions in NCC induction and migration (Fort et al, 2011;Guémar et al, 2007;Notarnicola et al, 2008). In addition, Rac1 promotes chick NCC migration and Rac activation is influenced by Rho (Shoval and Kalcheim, 2012). It will be important to determine how Rho family members function together in NCC EMT and to further uncover the diverse molecular processes that may be used by NCCs in different species and populations to ultimately carry out EMT.…”
Section: Research Articlementioning
confidence: 99%